Map showing Newfoundland Government railway and steamship system [September 1923] - Newfoundland Railway Company (St. John's, 1923)
Black and white. Dated September 1923. Relief shown by hachures and spot heights. Bar scale in miles. Shows rail and steamship lines. Includes ancillary map: Newfoundland map showing Newfoundland Government railway and steamship system. Includes timetables and tourist information. CNS map no. 239 (recto), 240 (verso)